Pemberdayaan UMKM di Desa Padi Melalui Deversifikasi Produk dan Pemasaran Online Bawang Goreng di Desa Padi Mojokerto - Eny Setyariningsih; Utami, Budi; Hidayat, M. Syamsul (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
Increasing family economic empowerment can start from simple things, things that can be done by people in the village by starting businesses that are simple, including what happened in Padi village, Gondang subdistrict. This service aims to help analyze the role of Micro, Small and Medium Enterprises (MSMEs) in developing the local economy in Padi Village, Gondang District, Mojokerto Regency, with a special focus on MSMEs processing fried onions. The method used in this service is a qualitative approach with observational interview techniques both with MSME actors in the Padi Village and with Mrs. Winayah as the owner of the Fried Onion MSME, and secondary data analysis. The research results show that fried onion MSMEs in Padi Village play a significant role in increasing local community income and creating new jobs, and according to the results of the SWOT analysis, Padi Village MSMEs have the potential to develop and improve if mentoring is carried out regularly and periodically. facing various challenges, such as limited human resource capabilities, marketing and technology. Efforts to develop MSMEs through government support and empowerment of local communities are identified as key strategies to increase the competitiveness and sustainability of these businesses. This Community Service Program is expected to provide a positive impact in innovation in shallot processing and product development, packaging improvements for a wider market, business management training, and development of marketing networks as important steps in supporting the growth of fried onion MSMEs in the Village. Paddy.